Modified Vancouver Scar Scale score is linked with quality of life after burn. Issue 4 (June 2017) - Finlay, Vidya; Burrows, Sally; Kendell, Rosemary; Berghuber, Aaron; Chong, Vincent; Tan, Jason; Edgar, Dale W.; Wood, Fiona
Highlights: The sample consisted mainly of small burns with low severity scars. Higher mVSS total scores were associated with lower BSHS-B total scores. Relationship of mVSS total to BSHS-B total was amplified by increased TBSA. Worse rated scars produced lower Affect and Relations domain scores in females. Pigmentation scores did not affect the overall relationship. Abstract: Introduction: This study aimed to determine if a scar quality is associated with quality of life (QoL) at six months post-burn and beyond. Methods: Quantile regression models adjusted for covariates were used to demonstrate the relationship of modified Vancouver Scar Scale (mVSS) total (with and without pigmentation) and the mVSS components, to the Burn Specific Health Scale-Brief (BSHS-B) scores (full scale, Affect and Relations domain, Skin Sensitivity domain). Results: The sample (n = 341) comprised 67% males, 83% with skin grafts with a median age 38 years, total body surface area (TBSA) 4%, length of stay seven days, mVSS total score of five and BSHS-B total score of 153. Between six and 12 months of injury, mVSS total, TBSA and female gender were significantly associated with the BSHS-B, a situation that was not affected by the presence or absence of pigmentation scores. The mVSS components did not individually influence QoL. Discussion: mVSS total score, gender and burn size data may be a useful adjunct to experienced clinical judgment for identifying at risk patients and directing appropriate, timely resource allocation.